PROFILING IN THE RECRUITMENT OF SUBJECTS FOR CLINICAL TRIALS IN THE LIGHT OF GDPR - Natalia Domagała; Bartłomiej Oręziak; Marek Świerczyński (Zeszyty Prawnicze)
Highly specialized methods of selecting participants for clinical trials have been in use for a long time in the medical sciences. An example is oﬀered by oncological pre-profling, which involves the use of genetic biomarkers for a preliminary identification of oncological patients for clinical trials. We should expect further developments in this area, due to the rapid progress being made in e-health technologies and patients’ growing use of mobile applications. Failure to use new technologies in recruitment could even lead to failure in carrying out a clinical trial due to a shortage of participants.